SURG-24. NOVEL MALLEABLE FORCIPES FOR ENDOSCOPIC ASSISTED TECHNIQUE IN PEDIATRIC BRAIN TUMORS. (4th December 2020) - Nakahara, Yukiko; Ito, Hiroshi; Yoshioka, Fumitaka; Inoue, Kohei; Ogata, Atsushi; Masuoka, Jun; Abe, Tatsuya
Abstract: Recent advances in optical devices and surgical instruments have been applied to neurosurgery. Even with modifications, one of the most serious risks is injury of neuronal and vascular structure caused by operation of surgical instruments in a narrow surgical field. Fixed instruments are not practical for pediatric brain tumor surgeries because the length of the curved or angled tip portion is limited because of the narrow entrance. We developed a novel malleable forceps to resolve the difficulties related to microsurgical procedures. The malleable forceps has two shafts with a sharp cup at the tip. The entire forceps was made of stainless steel, with a silver and nickel alloy inserted between 10 and 40 mm from the tip. In the alloy part, the surgeon can flex the forceps freely using a special cylinder. The special cylinder is useful to prevent from slipping of the cups of tip. The maximum angle that can be bent is 70 degrees vertically. We also developed a monoshaft malleable forceps. We used these flexible forcipes in the case of various pediatric brain tumors including craniopharyngioma. We performed tumor resection by anterior interhemispheric trans-lamina terminalis approach. After procedure of tumor resection using microscope, endoscope inserted around the pituitary stalk. The piece of calcified tumor could be easily removed without any complications. These forcipes can be deformed to an appropriate angle and can be applied to various cases, especially pediatric brain tumors.